Dehydroascorbic acid-induced endoplasmic reticulum stress and leptin resistance in neuronal cells - Thon, Mina; Hosoi, Toru; Ozawa, Koichiro (Biochemical and biophysical research communications, 2016)
Due to its anti-obesity effects, an adipocyte-derived hormone, leptin, has become important for the treatment of obesity. However, most obese subjects are in a state of leptin resistance, and endoplasmic reticulum (ER) stress is suggested to be involved in the pathophysiology of leptin resistance. Dehydroascorbic acid (DHAA), an oxidized form of vitamin C, was found to be increased in diabetes. In the present study, we investigated the possible effects of DHAA on the activation of ER stress and leptin resistance. A human neuroblastoma cell line, stably transfected with the Ob-Rb leptin receptor (SH-SY5Y-ObRb), was treated with DHAA. We found that DHAA upregulated ER stress-related genes such as GRP78, CHOP, and spliced XBP1. Moreover, leptin-induced STAT3 phosphorylation was hindered by DHAA. These results suggested that increases in the levels of DHAA might be harmful to neurons, contributing to defective leptin-responsive signaling. •Dehydroascorbic acid (DHAA) induced endoplasmic reticulum (ER) stress.•DHAA inhibited leptin-induced signaling.•DHAA may be involved in the pathophysiology of leptin resistance by inducing ER stress.